Assistance with the Legalization of MSME Products in Gondang Village, Gangga District, North Lombok Regency - Damayanti, Sri; BudaYasa, I Putu; Azim, Muhammad; Syahrir, Syahrir; Uli, Aprilla Sinta; Farizi, Moh. Salman Al; Ahmad, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Assistance with the legalization of MSME products can provide knowledge to the public for sustainability as well as security and comfort for MSME activists both from a legal perspective and their position as products that are suitable to compete in national or global markets. The focus of this research is on the factors behind the defects in the identity of products produced by MSME activists in Gondang Village, Gangga District, North Lombok Regency. The method used in this research is qualitative by collecting data through interaction. directly with MSME activists to then provide an explanation regarding the importance of legalization of MSME products. primary (community) and secondary data sources (books related to MSME product regulations)